2018
DOI: 10.1002/path.5081
|View full text |Cite
|
Sign up to set email alerts
|

Somatic POLE exonuclease domain mutations are early events in sporadic endometrial and colorectal carcinogenesis, determining driver mutational landscape, clonal neoantigen burden and immune response

Abstract: Genomic instability, which is a hallmark of cancer, is generally thought to occur in the middle to late stages of tumourigenesis, following the acquisition of permissive molecular aberrations such as TP53 mutation or whole genome doubling. Tumours with somatic POLE exonuclease domain mutations are notable for their extreme genomic instability (their mutation burden is among the highest in human cancer), distinct mutational signature, lymphocytic infiltrate, and excellent prognosis. To what extent these charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 41 publications
3
71
0
Order By: Relevance
“…In support of this, we observed a trend of higher somatic mutation burden in OC patients with germline ANKRD11 and POLE ‐mutations. This finding is consistent with what has been observed in endometrial and colorectal tumors with somatic POLE ‐mutations . In addition, it might also raise the beneficial potential of including POLE in gene panel testing of OC patients and their family members in order to optimize the prevention strategies to decrease their risk of OC and colorectal cancer.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In support of this, we observed a trend of higher somatic mutation burden in OC patients with germline ANKRD11 and POLE ‐mutations. This finding is consistent with what has been observed in endometrial and colorectal tumors with somatic POLE ‐mutations . In addition, it might also raise the beneficial potential of including POLE in gene panel testing of OC patients and their family members in order to optimize the prevention strategies to decrease their risk of OC and colorectal cancer.…”
Section: Discussionsupporting
confidence: 88%
“…Our finding is consistent with recent findings that POLE mutations can contribute to susceptibility to a broad cancer spectrum including OC. 34,35 Furthermore, it has also been reported that POLEmutant endometrial and colorectal tumors had a high somatic mutation burden, elevated expression of immune checkpoint genes and increased lymphocytic infiltration, [36][37][38][39][40][41][42][43] and therefore immune checkpoint inhibitors was recommended for treating cancers with POLE-mutations. 41,44 Similar recommendation was also demonstrated in mismatch repair (MMR) deficient cancers regardless of the cancers' tissue of origin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the presence of TIL is associated, albeit imperfectly, with clinical response to immunotherapies targeting the CTLA-4 and PD-1 pathways, referred to as "checkpoint blockade" (5)(6)(7). TIL responses generally show a positive association with mutation load, presumably due to an increased number of mutated antigens (neoantigens) available for T-cell recognition (8,9). In addition, DNA damage can promote TIL responses by activating mechanisms such as the cGAS/STING pathway (10), leading to an immunologically permissive tumor microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…Exonuclease domains of DNA polymerase δ ( POLD ) and Polymerase ɛ ( POLE ) are critical components of the normal DNA replication process and provide an essential proofreading function. Mutations in POLE and POLD occur in approximately 1% of colorectal cancers and have been associated with an ulltramutated tumor status (very high tumor mutation burden) and increased tumor PD‐L1 expression and infiltration with cytotoxic lymphocytes . These tumors are associated with a decreased risk of recurrence and are underrepresented in the setting of metastatic disease in comparison to earlier stages of CRC .…”
Section: Biological and Targeted Therapy In Mcrcmentioning
confidence: 99%